Apparent differences between human and chimp proteomes are reduced when considering human population: Human specific variants are enriched in disordered and compositionally biased regions - Pablo Mier; Miguel A. Andrade-Navarro; Enrique Morett (PLoS ONE, 2025)
Humans exhibit significant differences from other primates in anatomy, physiology, behavior, and culture, despite having similar genomes. Understanding the genetic basis of these unique human traits has long been a goal of science and philosophy. Previous studies, including the comparison of the reference genomes, showed a high degree of sequence identity between the proteomes of humans and chimpanzees (Pan troglodytes), suggesting that differences may lie in gene regulation rather than protein function. To pinpoint human-specific protein mutations with possible relevance for human-specific traits, we went further in the study of human-chimp proteome differences by taking into account human genetic variation data from the Genome Aggregation Database (gnomAD) at protein-coding genes. We additionally included 11 primate genomes to identify human-specific amino acids. Results showed that human-specific positions were dramatically reduced when considering population diversity. Our analysis identified 6210 human-specific amino acid substitutions across 4475 proteins. Interestingly, these residues are enriched on disordered and compositionally biased regions, suggesting a role in protein regulation instead of a catalytic or structural one. Accordingly, the set of proteins holding them was significantly enriched in proteins with disordered regions and with protein binding functions. We found that a subset of these residues is not only different in humans but also conserved across non-human primates, further supporting their potential importance in making us different from other primates.